Smart control of UPCQ within microgrid energy system - Benachaiba, C.; Haidar, Ahmed M. A.; Habab, M.; Abdelkhalek, O. (Elsevier Ltd, 2011)
One of the most popular issues in the future power distribution is the quality improvement of microgrid and the development of smart grid (SG). Many applications operating at the microgrid level can be considered as smart grid functions. This paper proposes the application of Fuzzy Logic (FL) technique within microgrid energy system based on the most modern power conditioning equipment devices such as Unified Power Quality Conditioner (UPQC). This technique is working together with the microgrid to track the disturbance of the smart grid and improve the quality of the system with a high flexibility. Furthermore, a control methodology developed based on a simulation technique to maintain the output voltage of the microgrid. Finally, experimental results show the high performance of the proposed Fuzzy Logic controller (FLC) compare to the classical proportional integration (PI).